Digitally-Enhanced Communication Competencies: Preparing the Next Generation of Healthcare Professionals: A Systematic Review - Anis Novitasari; Ari Indra Susanti; Dewi Marhaeni Diah Herawati; Nita Arisanti; Hadi Susiarno; Vita Murniati Tarawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2026)
The adoption of digital technologies such as telehealth in health education requires the development of digital communication competencies among future healthcare professionals. Although health students generally demonstrate positive attitudes toward digital health, their readiness and practical communication skills remain limited. This systematic review aimed to identify the role of digital interventions in improving communication competencies (knowledge, skills, and attitudes) and to describe the characteristics of their implementation. A systematic search was conducted in five databases (PubMed, EBSCOhost, ScienceDirect, Scopus, and Sage Journals) for primary studies published between October 2020 and October 2025 following the PRISMA 2020 guidelines. Twelve studies met the inclusion criteria, with most conducted in the United States (41.7%) and Germany (25.0%), and the majority using quantitative designs (58.3%). Digital interventions—including telehealth modules, telemedicine simulations, telenursing training, virtual OSCEs, and video-based learning—consistently improved communication competencies. Knowledge scores increased significantly, with post-test scores reaching 57.1% in digital module interventions and telenursing knowledge scores increasing from 6.84 to 8.42 (Cohen’s d = 0.76). Communication skills also improved, with 100% of participants applying the Ask–Tell–Ask strategy after training and 98% recommending telemedicine simulation courses. Attitude outcomes showed increased confidence and readiness, with preparedness for telehealth rising from 37% to 78% and telenursing training demonstrating a large effect size (Cohen’s d = 1.04). However, ethical competencies, particularly informed consent, patient privacy, and virtual physical examination, remained relatively weak across studies. These findings suggest that digital interventions are effective in strengthening communication competencies among health students, but sustainable competency development requires structured integration of telehealth curricula with simulation-based learning, supervised practice, and explicit training in ethical and patient-centered communication.